2020
DOI: 10.1007/s11695-020-05049-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Quality of Life Outcomes After Laparoscopic Sleeve Gastrectomy and Roux-en-Y Gastric Bypass—a Comparative Study

Abstract: Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) have been shown to improve metabolic comorbidities as well as quality of life (QoL) in the obese population. The vast majority of previous studies have investigated the metabolic effects of bariatric surgery and there is a dearth of studies examining long-term QoL outcomes post bariatric surgery. The outcomes of 43 patients who underwent bariatric surgery were prospectively assessed, using BAROS questionnaires to quantify QoL and metabolic status pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The reason for the increased score is simply based on the high conversion rate, as patients converted due to weight regain were not included in this analysis and weight loss has a major impact on this score. A recently published study by Fiorani C. et al reported a BAROS of 1.47 at an 8-year follow-up after SG [21].…”
Section: Outcome and Quality Of Lifementioning
confidence: 92%
“…The reason for the increased score is simply based on the high conversion rate, as patients converted due to weight regain were not included in this analysis and weight loss has a major impact on this score. A recently published study by Fiorani C. et al reported a BAROS of 1.47 at an 8-year follow-up after SG [21].…”
Section: Outcome and Quality Of Lifementioning
confidence: 92%
“…Bariatric surgery causes significant changes in patients' life, including HRQoL. There is a growing body of literature demonstrating an improvement of both the physical and psychological status of the patients following bariatric procedures [2].…”
Section: Key Pointsmentioning
confidence: 99%
“…On the other hand, both in this study and in the one from Canada, the contribution of protein in the diet increased in the SWL group and was very close to the 5% significance level. This suggests that the role of proteins should be further explored, considering that in the Swedish study, protein played a relevant role in the analyzed isoenergetic diets, either because of its greater satiety effect 23 or perhaps because of the anatomical barrier produced by surgery, which may impact meat consumption. A relevant aspect in the context of weight loss by bariatric surgery is that some groups have insisted on ensuring a minimum protein intake of 60 g per day through supplementation in order to ensure muscle reserves, promote continued weight loss, and prevent osteoporosis 34 .…”
Section: Discussionmentioning
confidence: 99%
“…maintained to preserve historical comparison 23 . Although less sensitive, this instrument can identify impairment in the quality of life caused by a low weight regain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation